2007
DOI: 10.1038/ncb1640
|View full text |Cite
|
Sign up to set email alerts
|

Prometaphase APCcdh1 activity prevents non-disjunction in mammalian oocytes

Abstract: SummaryThe first female meiotic division (MI) is uniquely prone to chromosome segregation errors through non-disjunction, resulting in trisomies and early pregnancy loss1. Here, we show a fundamental difference in the control of mammalian meiosis which may underlie such susceptibility. It involved a reversal in the well-established timing of activation of the AnaphasePromoting Complex (APC)2, 3 by its co-activators cdc20 and cdh1. APC cdh1 was active first, during prometaphase I, and was needed in order to all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
117
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(128 citation statements)
references
References 31 publications
9
117
0
Order By: Relevance
“…In contrast, analysis of fluorescently labelled constructs in mouse oocytes showed that degradation of cyclin A2 did not occur any earlier than that of securin in late MI (McGuinness et al 2009, Jin et al 2010. This would be consistent with APC/C Cdh1 -mediated proteolysis restricting Cdc20 accumulation to late MI (Reis et al 2007), thereby preventing earlier prometaphase cyclin A2 degradation. It is noteworthy, however, that levels of endogenous cyclin A2 detected by immunoblotting in a recent paper appear to decline ahead of securin (see Fig.…”
Section: Apc/c-mediated Control Of M-phase Progressionmentioning
confidence: 78%
See 3 more Smart Citations
“…In contrast, analysis of fluorescently labelled constructs in mouse oocytes showed that degradation of cyclin A2 did not occur any earlier than that of securin in late MI (McGuinness et al 2009, Jin et al 2010. This would be consistent with APC/C Cdh1 -mediated proteolysis restricting Cdc20 accumulation to late MI (Reis et al 2007), thereby preventing earlier prometaphase cyclin A2 degradation. It is noteworthy, however, that levels of endogenous cyclin A2 detected by immunoblotting in a recent paper appear to decline ahead of securin (see Fig.…”
Section: Apc/c-mediated Control Of M-phase Progressionmentioning
confidence: 78%
“…Following the establishment of kMt attachments, SAC-mediated inhibition dissipates, thereby allowing activation of APC/C Cdc20 , which could then be tasked with degrading not only cyclin B1 and securin but also cyclin A2 and cyclin B2 (Touati et al 2012, Gui & Homer 2013. It should be noted that APC/C Cdh1 -mediated regulation of APC/C Cdc20 through Cdc20 proteolysis (Reis et al 2007) is not depicted here. Following exit from MI, Emi2 limits APC/C Cdc20 activity allowing for cyclin B1 accumulation and spindle stabilisation in MII (Madgwick et al 2006).…”
Section: Apc/c-mediated Control Of M-phase Progressionmentioning
confidence: 99%
See 2 more Smart Citations
“…MPM2 antibody was deployed here to track serine and threonine phosphorylated protein epitopes known to be phosphorylated by M-phase kinases during mitosis [25,26]. This antibody has been used in our laboratory for the identification of M-phase protein phosphorylation in oocytes as they acquire meiotic competence and undergo meiotic progression [21,27], transition states in the cell cycle that are known to be accompanied by gradual activation of H1 kinase that occurs during GVBD [28]. These studies extend that work identifying unreported dynamics of the MPM2 labeled phosphoproteins.…”
Section: Intracellular Localization and Dynamics Of Protein Phosphorymentioning
confidence: 99%